Gender Differences in Customer Behaviour in the Aspect of Odd-Even Pricing - T. Lepeyko; A. Kotlyk; E. Omarov (International Journal of Supply Chain Management, 2019)
This paper describes the experiment conducted in order to support or reject the hypothesis that the effect of the odd pricing technique depends on the gender of the customer. Analysis of the recent studies in the field of customers’ price perception and, more narrowly, the odd-even pricing, failed to formulate the mutually shared point of view on the problem: whether the odd pricing effect exists or not? Empirical evidence from one group of researches prove this effect is significant while other group of researches prove the opposite. This led scholars to the conclusion there are some individual and contextual factors impacting price perception by customers. So we assume one of these factors is gender. In this study, we have made 2 samples including 3 grocery shops each: initial settings and control settings. During all the experiment we were registering the gender of buyers who were purchasing goods from the predetermined list accounting 10 items (for the experiment there were chosen the goods which are well known by the customers, frequently bought, and normally bought in a similar amount by both genders). As a result of the experiment, we’ve found a significant difference in odd pricing effect among genders: female customers are more perceptive to it comparing to male customers. Keywords— Pricing, price perception, odd pricing, odd-even pricing, price ending, gender differences in price perception.